Tingkat Prediksi Pendaftar Ujian Kompetensi Laboratorium Menggunakan Metode Least Square - Gunadi Bin Senitio; Julius Santony; Jufriadif Na’am (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Services for laboratory competency test participants must be increased for each period. With the number of participants fluctuating, the laboratory must prepare and predict how many facilities will be used to support these activities, such as laboratory rooms, exam questions, and other equipment. To overcome this problem, a method is needed to predict the number of participants in the coming period. In this study, the Least Square method is used to predict participants in the next period. This method managed to get the number of predictions in the coming period with a prediction error rate of 9.99% using the Mean Absolute Percentage Error (MAPE). The empirical results show that this research is very helpful for the laboratory in preparing laboratory competence examination facilities